A Lab Scale Study on the Effects of Waste Lubricating Oil to Red Tilapia Oreochromis sp. Juveniles - Hassan, Ruhana; Salim, Sa’adiah; Ismail, Nurul Jannah; Ismail, Abdul Razak (Borneo Journal of Resource Science and Technology, 2016)
Waste lubricating oil is defined as used lubricating oil removed from internal combustion engines. Among the sources of this chemical are vehicles, mining, agricultural, industrial and construction equipment. Rapid industrialisation, urbanisation and increase in volume of transportation have increased environmental risks to aquatic organisms and human health for example improper disposal of waste lubricating oil into environment has affect human via bioaccumulation and biomagnification processes, besides direct impact on the aquatic ecosystem. A lab scale study was conducted to determine the effect of waste lubricating oil on red tilapia Oreochromis sp. juveniles. In this toxicity test, Oreochromis sp. juveniles were reared in a static system and subjected to four different concentrations of waste lubricating oil (50 ml/L, 90 ml/L, 120 ml/L and 200 ml/L) and observed for 96 hours. The lethal concentration, LC50 of waste lubricating oil in this study was 91.20 ml/L. There was a significant difference in the effects of waste lubricating oil on the mortality rate of Oreochromis sp. among treatments. Mortality of fish has strong positive correlation with concentration of waste lubricating oil added to the tanks. Swimming performances of test fish were reduced after 24 hours exposure to waste oil lubricants concentrations of 120 and 200 ml/L. Severe inflammation was observed on the kidney tissues of exposed fish after 96 hours experiment. Overall, water temperature and dissolved oxygen values recorded during toxicity test were constant and within the range for optimum values culturing tilapias. However mean pH value decreased from 7.19 to 5.33 as the concentrations of waste lubricating oil increased. This study only involved Oreochromis sp. juveniles as test fish; in future, study should also include other fish species. Findings reported here is limited to lab scale study, therefore the actual effects of waste lubricating oil deposited in the wild ecosystem is still unknown and need further investigations.